HUBUNGAN ANTARA KEBIASAAN MEMBACA DENGAN KEMAMPUAN MENULIS KARANGAN DESKRIPSI SISWA KELAS IV SDN TAMAN CIBODAS - Amalia Sri Wulandari; Sumiyani; Erdhita Oktrifianty (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The purpose of this study was to determine the relationship between reading habits and the ability to write descriptive essays of grade IV students. This type of research is descriptive quantitative where the results of this study can describe the results of the relationship between reading habits and the ability to write description essays. The data collection techniques used are questionnaires and tests. This research was analyzed using SPSS 25.0. The results of the study The level of reading habits is moderate, students in the moderate category are in the interval 60-84 with a total of 22 students, the level of ability to write descriptive essays is moderate, students in the moderate category are in the interval 60-84 with a total of 20 students, there is a significant relationship between reading habits and the ability to write student descriptive essays. The relationship is shown by the correlation coefficient (tcount) of 6.550 greater than the t table 1.697 at a significance level of 5% sig value of 0.000 <0.05 which means Ho is rejected and H1 is accepted.   Keywords: description essay, reading habits, writing skill